MENGENAL EQUATION OF TIME, MEAN TIME, UNIVERSAL TIME/ GREENWICH MEAN TIME DAN LOCAL MEAN TIME UNTUK KEPENTINGAN IBADAH - Misbah Khusurur; Jaenal Arifin (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2014)
Regular cycle of day and night due to the rotation of the earth creates a difference time regions. The earlier area facing the sun has earlier time than the western side (M.Syahudi Islami , 48). For example, when Semarang is in the time of maghrib, in Lampung maghrib has not yet come since it is in the western side. Likewise, by the times of sunrise in Lampung, the sun has already high in Semarang. The time difference is about 1 hour every 15 degrees of longitude, or 4 minutes for every 1 degree of longitude. The calculation is drawn from required time for one rotation (360 degrees) for 24 hours. This paper will explain about equation of time, mean time, universal time/Greenwich Mean Time, ad local mean time which are vital aspects for religious prayers, especially for calculating prayer schedule.Keywords: rotation,time, prayer